Identification and prevalence of pathogenic bacteria Vibrio sp in mangrove crabs (Scylla serrata) in Meuraxsa Sub-district, Banda Aceh City - Islamia, Ukhwatin; Islama, Dini; Zulfadhli, Zulfadhli; Diana, Fara; Yulianti, Devi (Universitas Malikussaleh, 2025)
Mangrove crab (Scylla serrata), is one of the fishery commodities that has high economic value. This is because it tastes good and has high protein, around 52%. Mangrove crab cultivation is a cultivation technology that requires a relatively short time, which is around 15-30 days of maintenance with a low mortality rate of around (10 - 20). Diseases in mangrove crabs can be caused by fungi and bacteria. One of the obstacles in mangrove crab fattening activities is the occurrence of death during the maintenance process caused by bacterial disease attacks, so efforts are needed to prevent disease. Therefore, research is needed to determine the Identification and Prevalence of Pathogenic Bacteria (Vibrio sp.) In Mangrove Crabs in the City. This research was conducted in November 2023. Sampling was carried out when the crabs were molting based on the results of the study of mangrove crabs in Meuraxsa District, namely Vibrio sp. bacteria. The highest prevalence value of vibrio sp bacteria is isolate code A and C in Muraxsa District, Banda Aceh City, at 40% with the normal/moderate infection category. Water quality parameters at the cultivation location are still within the optimal range for cultivation.Keywords: Bacteria; Mangrove crabs; Identification; pathogenic; Prevalence